Upaya Mengenali Sindrom Kardiometabolik melalui Pengabdian kepada Masyarakat - Dwi Novitasari; Dwi Agus Yulianto (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: The Healthy Adjusted Life Expectancy Index (HALE) for 2019 for the Indonesian population is 62.8 years lower than the 71.3 years for standard life expectancy; this is due to the lack of quality of life in Indonesia. The profile of the population in Central Java for the elderly category every year is similar to the increase on a national scale. The fact that the elderly are still working to earn a living indicates that their welfare level is still low. Non-communicable diseases (NCDs) are often the cause of premature death before the age of 70. Cardiovascular disease is the number-one killer in the world. Cardiometabolic syndrome is characterized by at least three things: abdominal obesity, increased plasma glucose, increased blood pressure, increased triglycerides, and decreased HDL cholesterol. A study on five members found an average total cholesterol level of 168.9 mg/dl and an average blood pressure of 125.4/80.9 mmHg. Objective: The aim of this community service is to increase awareness and the health status of members of the hypertension care group in Mersi Purwokerto. Methods: This community service method involves coordination with the chief of the hypertension care group, making leaflets, and preparing tools and materials for cholesterol examination. Results: This community service received good active participation from members of the hypertension care group in Mersi, Purwokerto. Overview of the risk of metabolic syndrome in community service participants, namely 32 DM sufferers (55.2%), 25 hypertension sufferers (43.1%), and 45 with high total cholesterol levels (77.6%). Conclusion: The results of this community service are expected to be a screening for participants who have a high risk of cardiometabolic syndrome and a desire to continue to make active and healthy lifestyle changes.